Students’ Humanistic Position Formation in the Educational Process - Shar, Svitlana O.; Vorona, Larisa I.; Kalinichenko, Iryna O.; Lebedyk, Lesia V.; Olifira, Larisa M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The student's humanistic position is not only the result of the teacher's personal influence but also a controlled process. As a result of the implementation of this process, the student receives an understanding of what should relate to the humanistic process and the humanistic function of society. Background: The basis for the formation of humanism for all participants in the students' educational process is determined either by the teacher's position or by the installation in the pedagogical process. So, any impact on the part of the teacher can be perceived as an exceptional factor of influencing the student's personality, which can be perceived as a compulsory education requirement. Method: Assessment of pedagogical effectiveness was carried out by means of an expert survey. Diagnostic and processing of empirical data was carried out according to the methodology for assessing the importance of each individual requirement for the proposed educational materials. Results: The study examines the components that form the student’s humanistic position on the basis of the traditional components of the formation of the pedagogical teaching strategy. The practical significance of the study is determined by the fact that it is possible to implement the concept of the formation of active skills in students during certain actions and the formation of other humanitarian positions. Conclusion: The study shows that the level of formation of the students' humanistic position concerning all participants in the educational process depends on updating the educational process of training specialists based on the developed theoretical and methodological foundations.